Women leaders in the political field in Scotland: A socio-historical approach to the emergence of leaders. (December 2018) - Robinson, Sarah; Kerr, Ron
Drawing on a contextualised case, we present a specific approach to leadership studies that brings together history, sociology and politics. We start with the following event. In August 2015, the election of Kezia Dugdale as leader of the Labour Party meant that, for the first time the leaders of the three main political parties in the Scottish Parliament were women. We approach the study of this significant leadership event, first, through a critique of aspects of leadership studies as a field. We next consider the potential for socio-historical approaches in understanding this event. Then, as a contextualised example of this alternative approach to studying leadership, we apply Bourdieu's theoretical concepts – in particular the political field – in order to historicise the conditions of possibility of this event. Finally, we consider issues of power and gender in relation to how the leaders position themselves in relation to their parties and to each other within the political field. In so doing, we contribute to critical leadership studies by developing and demonstrating a socio-historical approach that can help us to identify processes of organisation and change in relation to the emergence of leaders.